Seasonal Variations in Macroinvertebrate Diversity and Community Composition in Kamala River of Churia Range, Nepal - Tachamo-Shah, Ram Devi; Shah, Deep Narayan; Pandey, Anusha; Maharjan, Junu; Doody, Tanya M; Cuddy, Susan (Journal of Institute of Science and Technology, 2024)
Macroinvertebrates have long been utilized in the ecological assessment of streams and rivers as they respond to multiple stressors present in aquatic environments. However, the application of macroinvertebrates as bioindicators in the assessment of hydro-morphologically degraded rivers in Nepal is limited. Therefore, we studied the macroinvertebrate diversity and community composition in 10 sites along the Kamala River and its tributaries, one of the hydro-morphologically degraded rivers in the Churia range of central Nepal, during the winter and spring seasons of 2019. The elevation of the sites ranges from 60 m asl to 636 m asl. Twelve water quality parameters and three hydrological parameters were measured for each site in addition to macroinvertebrates data. Water temperature (winter- 19.3 ± 2.2 ⁰ C; spring- 31.3 ± 2.3 ⁰ C), pH (winter- 8.7 ± 0.5, spring- 7.4 ± 0.5), turbidity (winter-3.0 ± 3.8 NTU, spring- 22.9 ± 22.8 NTU), total alkalinity (winter-156 ± 70.7 mg/L, spring- 33.8 ± 6.0 mg/L), phosphate (winter-3.0 ± 1.8 mg/L, spring- 0.4 ± 0.3 mg/L) and river discharge (winter- 2.01 ± 0.75 m3/s, spring- 0.77 ± 0.28 m3/s) differed significantly between seasons (p<0.05). In total 62 taxa representing 42 families and 13 orders for winter season and 69 taxa representing 49 families and 18 orders of macroinvertebrates were recorded for spring season. NMDS revealed two distinct clusters based on macroinvertebrates abundance data for the river. Ephemeroptera, in particular Baetis spp., Torleya coheri and Caenis sp., and Trichoptera- Chuematopsyche spp. were the major taxa contributing to dissimilarity across sites between seasons.